Peran Generasi Muda Dalam Mendorong Pertanian Berkelanjutan: The Role of the Young Generation in Promoting Sustainable Agriculture - Gusya, Irsyad M.I; Rozaki, Zuhud; Wulandari, Retno; Amanah, Cantika Wira (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2024)
Empowering the younger generation in agriculture is an urgent need to ensure the sustainability of the sector. The agricultural sector has a strategic role in national economic development, and sustainable agricultural development requires quality human resources. A focus on the younger generation is key to ensuring a strong future for agriculture. Agricultural education needs to be improved, covering vocational to higher-level education, to encourage the participation of the younger generation. Empowerment involves access to quality education, training and field experience. Promotion of sustainable agriculture is important, especially for farmer regeneration. Technological innovation has a big role, with the understanding and application of innovative technologies can increase agricultural productivity. Sustainable agricultural development planning should include economic, environmental and farmer welfare aspects. Innovative agricultural institutions are also key in achieving food security. The involvement of rural youth and the role of young farmers is crucial, with the potential to shift the agricultural paradigm towards more efficient and sustainable practices. Empowering young farmers involves not only technology, but also education, access to capital, and policy support Through the spirit of innovation and collaboration between the government and the private sector, we can create an enabling environment for the development of young farmers as a key pillar in achieving sustainable agriculture, building the foundation for a brighter agricultural future that is responsive to global challenges.